THE ERRORS OF SPEECH PRODUCTION IN DORY’S UTTERANCES OF FINDING DORY MOVIE - Vahlevi, Reza; Natsir, M.; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
This study is aimed to find out the errors of speech production in Dory’s utterances of Finding Dory movie. The theory used to find out the errors of Dory’s speech production was Levelt’s model of speech production (1999): conceptualisation, formulation, articulation, and self-monitoring. Words in the form of dialogues (Dory’s utterances when her short-term memory loss appeared only) were the data in this study. The research design of this study was qualitative.  The results showed the errors of speech production in Dory’s utterances were identified into five types such as words substitution, contradictory utterance, similar words rhyming, incomplete utterances, and hesitation utterance. The most affected stage by Dory’s short-term memory loss was conceptualisation. It was because during the times when short-term memory loss appeared, Dory realised that her disorder infiltrating the stage that made her to be unsatisfied and as the result, she retracted and performed her utterances from the beginning many times. Therefore, this study concluded the errors that Dory produced in her speech production were all caused by the interference of short-term memory loss.